Landscape lexical diversity for readability and safety mitigation on the commuter line bilingual information board - Nuruz Zaman Mochamad; Supriatnoko; Naufal Alhilmy Muhammad (E3S Web of Conferences)
This study examines lexical diversity and readability of bilingual information boards on the Commuter Line Tanah Abang-Rangkasbitung in Indonesia, with a focus on their impact on passenger safety. It is motivated by observed discrepancies in translations, which could compromise clarity and effectiveness of public signage. The primary objective is to analyze lexical diversity and assess the readability of these translations using theoretical frameworks from Nida and Taber (2003), Newmark (1988), and Venuti (2012). The study employs a qualitative descriptive research design with Spradley’s Ethnographical Approach, focusing on the Green Ring Route, which encompasses 19 CL stations. Data were collected through direct observation, photographic documentation, and field notes and analyzed using domain, taxonomy, componential, and cultural theme. The findings reveal significant variation in readability levels, influenced by the translation techniques used. High readability was found in translations employing Literal Translation and Established Equivalent techniques, while medium and low readability were associated with Borrowing, Modulation, and Amplification techniques. These findings underscore the need for consistent, culturally relevant translation practices to ensure effective communication and passenger safety. The study concludes by recommending regular usability testing, feedback integration, and use of technology to enhance the accessibility and effectiveness of bilingual signage in public transportation.